Radiographic Investigation of Root Canal Morphology of Permanent Mandibular Molars in Makkah Population (Saudi Arabia) Using Cone-Beam Computed Tomography - Laila Mohamed Mohamed Kenawi; Raghad Fahad Althobaiti; Dina Mohammad Filimban; Sarra Dakheel Allah Alotaiby; Majedh Awad Alharbi; Wed Mohammed Kassar (International Journal of Dentistry)
Objectives. This study aimed to analyze the root canal morphology of first and second permanent mandibular molars among Makkah population by using cone-beam computed tomography (CBCT). Materials and Methods. CBCT images of two hundred eight patients were obtained from the Faculty of Dentistry, Umm Al-Qura University, Makkah, Saudi Arabia. In all images, mandibular first and second molars were evaluated for the number of roots and their morphology, number of root canals, canal configuration in each root according to Vertucci’s classification, and the presence of a C-shaped canal. Results. Most of the mandibular first molars had two roots (96.5%) and three root canals (77.7%). Type IV canal configuration prevailed (75.6%) in the mesial roots, and type I canal configuration prevailed (71.7%) in the distal roots. For the mandibular second molars, the majority had two roots (96.3%) and three root canals (82.7%). Type IV canal configuration prevailed (48%) in the mesial roots and type I (99.1%) in the distal roots. C-shaped canals were detected in 5.7% of the mandibular first molars and 4% of the mandibular second molars. There was no statistical difference between the mandibular first and second molars (P>0.05) in the shape of the roots and the presence of the C-shaped canals. Conclusion. Most of the mandibular molars in Makkah population presented with two roots and three root canals. The incidence of three-rooted mandibular molars was low, and it was higher in the first molars than second molars. The type IV root canal system prevailed in mesial roots and type I in distal roots.